EFEKTIFITAS MATERNITY BRA DAN FLAT SHOES TERHADAP NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER II DAN III DI POLI BKIA RUMAH SAKIT ISLAM SURABAYA - Umamah, Faridah; Afiyah, R. Kahiariyatul (Universitas Pesantren Tinggi Darul Ulum, 2019)
AbstractAs the gestational age increases, the back of the pregnant woman turns to the shoulder pulled back as a result of enlargement of the protruding abdomen and to maintain body balance due to excessive curvature in the spine, commonly called lordosis. As the age of the fetus gets older the greater it becomes so that the curve of the lower back increases. This can also aggravate back pain. The use of maternity bras and flat shoes can reduce stretches on the back so that pregnant women can still be active. This study aims to analyze the effectiveness of Maternity Bra and flat shoes on back pain in second and third trimester pregnant women at the BKIA Poli Islamic Hospital in Surabaya.This research is a type of Quasi Experiment research. The target population is all second and third trimester pregnant women in the BKIA Poli Islamic Hospital in Surabaya. The research unit of 30 respondents was obtained through simple random sampling technique. The independent variable is maternity bra and flat shoes, while the dependent variable is back pain. Data collection on the use of maternity bras and flat shoes with a checklist, back pain data using a questionnaire. Data were analyzed using the Wilxocon Signed Rank Test and Man Whitney Test.Wilxocon statistical test results found that the use of maternity bras and flatshoes affect back pain in second and third trimester pregnant women, with Asymp.Sig values. (2-tailed) worth 0.001. With the whitney man test found that the use of flatshoes is more effective in reducing back pain compared to the use of maternity bras.The conclusion of this research is the use of maternity bras and flatshoes can reduce complaints of back pain in pregnant women at the Islamic hospital in Surabaya, therefore the use of maternity bras and flatshoes is highly recommended for pregnant womenKeywords: Maternity bra, Flatshoes, back pain and second and third trimester pregnant women